Dermoid cyst over the left sphenoid in a child: a rare case report - Kumar, Andrews Navin; Shivpuri, Anubhav; Mehta, Sandeep; Sambyal, Shanender Singh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
In this case report a bony swelling was noticed clinically which had a cystic presentation in CT imaging. After surgical removal it was sent for histopathological examination and was diagnosed as dermoid cyst. Dermoid cyst is rarely encountered lesions of head and neck region so most frequently misdiagnosed. Though this lesion is very rare but should be considered as a differential diagnosis while evaluation cystic lesions of head and neck region.